2016
DOI: 10.1515/revneuro-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory and inhibitory conversive experiences: neurobiological features involving positive and negative conversion symptoms

Abstract: AbstractPrevious reviews have focused on neurobiological and physiological mechanisms underlying conversion disorder, but they do not usually distinguish between negative and positive conversion symptoms. Some authors have proposed that different phenomena should underlie both situations and that diverse emotion regulation strategies (under- vs. overregulation of affect) should be related to different internal experiences (excitatory experiences with hyperarousal manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In another study using the DERS and Affective Style Questionnaire, it has been shown that patients diagnosed with PNES had higher levels of emotional dysregulation compared with healthy controls (Krámská et al, 2020). Negative conversion symptoms such as deafness, hysterical paralysis, aphonia, blindness, and sensory loss and positive conversion symptoms such as pseudoseizures, gait disturbances, excessive activity manifested by aberrant movements, and psychogenic tremors have been associated with different neurobiological and physiological features and different emotion regulation strategies (Del Río-Casanova et al, 2016; Kozlowska et al, 2011; van Dijke et al, 2010). Studies conducted on patients with FNSD have found two main opposite patterns of emotion dysregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study using the DERS and Affective Style Questionnaire, it has been shown that patients diagnosed with PNES had higher levels of emotional dysregulation compared with healthy controls (Krámská et al, 2020). Negative conversion symptoms such as deafness, hysterical paralysis, aphonia, blindness, and sensory loss and positive conversion symptoms such as pseudoseizures, gait disturbances, excessive activity manifested by aberrant movements, and psychogenic tremors have been associated with different neurobiological and physiological features and different emotion regulation strategies (Del Río-Casanova et al, 2016; Kozlowska et al, 2011; van Dijke et al, 2010). Studies conducted on patients with FNSD have found two main opposite patterns of emotion dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…The first is that positive conversion symptomatic patients—known as hyperreactive patients—have poor affect regulation (underregulation of affect), are unable to manage their overwhelming emotions, and frequently feel hyperreactive. Second, patients with negative conversion symptoms are known as emotionally flattened patients and experience the overregulation of affect as a result of inhibitory experiences, and they are emotionally flattened and disconnected (Del Río-Casanova et al, 2016; Del Río-Casanova et al, 2018; Kozlowska et al, 2011; van Dijke et al, 2010). Another diagnosis in the category of somatic symptom and related disorders in DSM-5-TR is somatic symptom disorder (SSD).…”
Section: Discussionmentioning
confidence: 99%
“…However, emotional circuits, (mainly limbic networks), and their influence on the regulation ofcortico–striato–thalamo–cortical circuits, are thought to be relevant. 17 Classic psychedelics, which act through serotoninergic agonism, but have similar downstream effects to esketamine via glutamatergic neurotransmission, have recently been proposed as plausible candidates to treat FND. 18 , 19 One of the main theoretical frameworks in this regard lies in their capacity to influence neural networks, especially the default mode network.…”
Section: Discussionmentioning
confidence: 99%